Theoretical Dialogs About Ethical Issues in Knowledge Organization: Garcia Gutierrez, Hudon, Beghtol, and Olson - Chaves Guimaraes, Jose Augusto [UNESP]; Pinho, Fabio Assis; Milani, Suellen Oliveira [UNESP] (Ergon-verlag, 2016)
Considering the need for a constant questioning on the role of the information professional, more specifically with respect to the ethical aspects of their practice, this study discusses how information science has been addressing over the past decades the ethical aspects inherent to the field of knowledge organization. In this context, we discuss the concepts of interactive epistemography and transcultural ethics of mediation by Antonio Garcia Gutierrez, multilingualism in knowledge representation by Michele Hudon, cultural hospitality by Clare Beghtol and the power to name by Hope Olson, in their aspects of convergence, complementarity and dialogicity.
Keywords: knowledge organization; ethical; cultural; Garcia Gutierrez; Hudon; Beghtol; Olson